Doenças dos aminoácidos de cadeia ramificada. - A Cabral; R Portela; T Tasso; F Eusébio; I T De Almeida; C Silveira (Acta Médica Portuguesa, 1998)
The authors present 19 cases of branched-chain AA catabolism disease: 9 Maple Syrup Urine Diseases, 6 Methylmalonic Acidemias, 2 Propionic Acidemias, 1 case of 3-OH-3-methylglutaryl-CoA-lyase deficiency and another of 2-methyl-ketoacetyl-CoA-thiolase deficiency. Fifteen are early neonatal forms and in 4 the onset occurred later. Fifteen patients (78.9%) needed one or several extra-corporal procedures either in the initial acute phase or during relapse. Fifteen patients presented several metabolic relapses, sometimes fatal (3 children). Global mortality was 26.3%, that is 5/19 patients: 4 children with neonatal forms, one with a later onset. Eleven patients (57.9%) had an IQ/DQ > or = 80: only 46.6% of the neonatal forms obtained these results, in contrast with all the late onset forms. Of the survivors, 9 (64.2%), presented a residual neurologic condition. The correct diagnostic and treatment procedures are defined and the need to consider the existence of these diseases at any age, particularly in the neonatal period, is stressed.